Normoglycemic effect of the tuber and the yacón leaf (smallantus sonchifolius) in type 2 diabetic patients - Alfaro Ludeña, Clyff (2022)
The purpose of the present study is to establish the effect of the yacon tuber and leaf (Smallantus Sonchifolius) on the levels of the seric glucose and glycosylated hemoglobin with the consumption of an adlibitum diet. A blind, simple and experimental field-controlled trial was carried out for a period of 90 days in 30 subjects, in an age range from 26 to 90, who were diagnosed with Type 2 Diabetes Mellitus with no control despite the pharmacological treatment. The subjects were divided into 3 groups; the first group received 500g per day of fresh yacon fruit; the second group received freeze-dried yacon equivalent to 500 g per day of the fresh fruit, and the third group received yacon leaves tea bags (each tea bag containing the equivalent to 1 g of yacon leaves), which were taken three times a day.Regarding the glycosylated hemoglobin, the administration of the fruit, the tea bags and the freeze-dried yacon reduced an average of 1.98%, 1.84% and 1.14%, correspondingly, in each group. In the seric glucose we could observe a considerable drop in the fourth week in the three groups. The largest drop happened in the group that received the yacon tea bags and the lowest drop in the group that received the yacon fruit.We can conclude that the yacon, in its different presentations, produce a decrease of the seric glucose without reaching the normal values. It was also noticed that the changes in the concentration of the seric glu cose did not show a significant difference among the age groups nor in repeated measures of seric glucose among weeks nor in gender. A significant decrease of the final glycosylated hemoglobin regarding the basal was also shown in all the groups, finding a marked decrease in the group that received fresh yacon fruit.